Implementasi Metode WASPAS Dalam Penilaian Kinerja ASN Dengan Pembobotan Menggunakan Metode ROC - Arya, Raihan Dwi; Ardiansyah, Rian (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2024)
It is very important to assess ASN performance for resource management because it can be used for decision making in a policy. The aim of this research is to create a Decesion Support System for assessing ASN perfoance using the WASPAS method and ROC weighting. ASN performance assessments are carried out using methods based on assessing attendance and punctuality, so that the assessment process is still considered to be less effective in determining performance assessments. The result form the calculation of the highest ASN performance assessment were obtained by no.2 with a final score of 0.958 and ranked 1st in the ranking and no.1 hot the lowest score with a final score 0.906 and ranked 5th.